Anatomija bolečine - kaj pravi medicinska antropologija - Šimenc, Jana (Etnolog. Nova vrsta (Ljubljana), 2008)
Diseases and pain are the daily companions of our lives and because of the mystery of their appearance and manifestation they are a challenge to many sciences; a single science (e.g. biomedicine) indeed often fails to provide the clear and exact answers people expect. The slippery ground of disease and pain are the causes, which are not always clear or explained, and constantly provoke reflections about inadequately set criteria and established dualisms. The latter confine man in too narrow limits that are often transgressed by a single unexplained pain. The article is quite technical in nature and deals with the views of medical anthropology on the relationship between the soul and the body, the pathological and the normal. It further addresses the research and methodology prospects of this anthropological discipline and its contribution to the study of pain.
Keywords: ethnology; etnologija; medicinska antropologija; bolezen; telo; bolečina